Electrochemical and mechanical properties of low friction nc-CrC/a-C:H and nc-WC/a-C:H coatings on construction materials deposited by magnetron sputtering. - Grobelny, Marcin; Rudnik, Dariusz; Makowka, Marcin; Wlodarczyk-Kowalska, Katarzyna; Nolbrzak, Piotr; Pawlak, Wojciech (International Conference on Plasma Surface Engineering, 2013)
The increased focus on the natural environment protection, the increasing fuel prices and the will to reduce the costs of machines’ maintenance - all that obliges us to search for innovative engineering solutions that would both limit the use of conventional lubricants and enhance the machines’ efficiency. To fulfil this challenging goal, the parts of machines are coated with special low friction and high wear resistant materials more and more often. The PVD methods play a great role in this field. As the examples of coatings deposited by a PVD method and assuring the above mentioned goals may serve the nc-CrC/a-C:H and nc-WC/a-C:H. This research focuses on the electrochemical and mechanical studies of low friction nc-CrC/a- C:H and nc-WC/a-C:H coatings deposited by magnetron sputtering on two kind of construction materials: Vanadis 23 steel and oxygen hardened Ti-6Al-4V alloy. The obtained coatings were investigated using various electrochemical and mechanical methods. The following parameters of coatings were determines: electrochemical (corrosion resistance), micro-mechanical (nanohardness, Young’s modulus) and tribological (wear resistance, friction coefficient). The results presented in this paper have been obtained within the project “KomCerMet” (contract no. POIG.01.03.01-00-013/08 with the Polish Ministry of Science and Higher Education) in the framework of the Innovative Economy Operational Programme 2007-2013.